Prevalence of Tritrichomonas foetus and Campylobacter fetus subsp. venerealis among bulls slaughtered in the state of Minas Gerais, Brazil - Michele Placedino Andrade Botelho; Christian Hirsch; Andrey Pereira Lage; Christiane Maria Barcellos Magalhães da Rocha; Elaine Maria Seles Dorneles; Patrícia Gomes Cardoso; Geraldo Marcio da Costa (Semina: Ciências Agrárias, 2018)
Bovine genital campylobacteriosis (BGC) and bovine genital trichomonosis (BGT) are globally widespread, predominantly sexually transmitted diseases that mainly affect herds in which natural mating takes place. Bulls serve as good epidemiological indicators for studying the causative agents of these diseases in cattle herds. The objective of the present work was to determine the prevalence of BGC and BGT among bulls sent to slaughterhouses in southern Minas Gerais, Brazil. Samples of preputial smegma from 200 sexually mature, non-castrated bulls of several ancestries were collected in 2013 from four regional slaughterhouses. The polymerase chain reaction (PCR) was employed to detect Tritrichomonas foetus, Campylobacter fetus subsp. fetus, and C. fetus subsp. venerealis. Isolation also was used aiming to diagnosis of BGT. All smegma samples were negative in culture for T. foetus. Molecular tests revealed 8% (16/200) of animals to be positive for T. foetus, 17.5% (35/200) for Campylobacter. fetus subsp. fetus, and 13.5% (27/200) for C. fetus subsp. venerealis. The results of the present study indicate that T. foetus, C. fetus subsp. venerealis, and C. fetus subsp. fetus are present among bulls slaughtered in southern Minas Gerais, and that BGC and BGT occur in this region. These diseases therefore need to be considered during differential diagnosis of reproductive diseases affecting cattle herds in which natural mating is employed.